2020
DOI: 10.5565/rev/periferia.735
|View full text |Cite
|
Sign up to set email alerts
|

Emotional impact and upbringing of children under four years old during COVID-19

Abstract: La crianza genera oportunidades de aprendizaje e interacciones y la familia tiene una influencia directa en el desarrollo socioafectivo durante la infancia. La investigación analiza 682 respuestas de una encuesta realizada a familiares de menores de cuatro años, en situación de confinamiento, durante la pandemia del COVID-19 en España. Los objetivos son descubrir diversas prácticas de crianza e indagar sobre el impacto emocional. Los principales hallazgos muestran la utilidad de las rutinas, la realización de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
1
0
0
2
Order By: Relevance
“…Regarding the descriptive results obtained to meet the first objective of this study, it is globally confirmed that parents perceive a change in the habits of the infant-juvenile population. In particular, these results confirmed a change in the habits of the children-youth population, especially those related to difficulties in contact with peers and family members and sleep problems, coinciding with other studies (Berasategui Sancho et al, 2020;Brooks et al, 2020;Lee, 2020;Orgilés et al, 2020;Serrano-Martínez, 2020). As reviewed by Cifuentes-Faura (2020) school closures can lead to consequences, especially among the most vulnerable, related to eating insecurity or less healthy diets, less physical activity, and more screen use, with negative effects to their mental and physical health, made worse by interaction between changes in lifestyle and psychosocial stress caused by lockdown.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the descriptive results obtained to meet the first objective of this study, it is globally confirmed that parents perceive a change in the habits of the infant-juvenile population. In particular, these results confirmed a change in the habits of the children-youth population, especially those related to difficulties in contact with peers and family members and sleep problems, coinciding with other studies (Berasategui Sancho et al, 2020;Brooks et al, 2020;Lee, 2020;Orgilés et al, 2020;Serrano-Martínez, 2020). As reviewed by Cifuentes-Faura (2020) school closures can lead to consequences, especially among the most vulnerable, related to eating insecurity or less healthy diets, less physical activity, and more screen use, with negative effects to their mental and physical health, made worse by interaction between changes in lifestyle and psychosocial stress caused by lockdown.…”
Section: Discussionsupporting
confidence: 89%
“…La pandemia COVID-19 ha provocado un cambio en las rutinas diarias de trabajo, hogar y escuela, las familias y sus hijos han tenido que adaptarse a nuevas rutinas y situaciones, lo que ha podido incrementar o agravar el padecimiento de sintomatología emocional (Lacomba-Trejo et al, 2020); por eso, elaborar nuevas rutinas suele ser bastante útil. Las rutinas son un elemento clave que ayuda a organizar el tiempo dentro del hogar, mantiene un horario similar al periodo pre-pandemia y le da gran valor a los momentos destinados al descanso y al esparcimiento (Serrano-Martínez, 2020).…”
Section: Conclusionesunclassified
“…Por otro lado, un hecho que desencadenó un sin número de problemáticas recientemente, fue la pandemia por el COVID-19 que, a la hora de implementar medidas de mitigación sobre la propagación del virus, se han visto afectadas todas las actividades humanas como educación, empleo, turismo y congregaciones de todo tipo, sobre todo la socialización de los seres humanos a raíz del aislamiento social (Medina y Jaramillo-Valverde, 2020). Con énfasis en el sistema familiar, las dinámicas se vieron influenciadas negativamente, debido a la falencia en los procesos de adaptación al tener que asumir otras responsabilidades en el interior de las familias (Serrano-Martínez, 2020).…”
Section: Introductionunclassified